Composition for secondary battery binder, secondary battery binder and electrode using the same

KR103020001B1Active Publication Date: 2026-09-18PI SOLUTION TECH INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020240014221
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-30
Publication Date
2026-09-18
Estimated Expiration
2044-01-30
Patent Text Reader

Abstract

The present invention relates to a composition for a secondary battery binder comprising: (A) a crosslinkable monomer comprising an alkylene oxide unit; and (B) one or more polymers selected from (b1) a mixture of polyvinyl alcohol and polyacrylic acid, (b2) a polyvinyl alcohol-graft-polyacrylic acid copolymer, (b3) a polyvinyl alcohol-graft-polyacrylic acid-co-polyalkylene glycol (meth)acrylate copolymer and salts thereof; wherein a binder prepared from a composition according to one embodiment can satisfy excellent mechanical properties, adhesion, and ion conductivity characteristics when applied to an electrode of a secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present disclosure relates to a composition for a secondary battery binder, a secondary battery binder using the same, and an electrode. Background Technology

[0002] With the recent increase in technological development and demand for mobile devices, the performance requirements for secondary batteries are becoming increasingly sophisticated. To meet this demand, active research is underway to develop secondary batteries with high energy density and excellent lifespan and cycle characteristics through the development of various materials constituting the battery. Among these, electrode binders are a key material that improves battery performance, safety, and lifespan by fixing the positive and negative active materials to the battery structure and facilitating ion transfer between the electrode materials.

[0003] Meanwhile, conventional secondary batteries generally suffer from a problem where charge and discharge capacities decrease as cycles progress. One of the causes of this phenomenon may be the failure to adequately control separation between the electrode active material and the current collector, detachment of the electrode active material, or volume expansion of the electrode due to insufficient durability of the binder. Although research is ongoing to improve the adhesion and mechanical properties of electrode binders to solve the above problems, electrode binders with improved mechanical strength and adhesion have limitations, such as restricting the free movement of ions or failing to respond to volume changes in the electrode material due to reduced flexibility.

[0004] To improve the stability and performance of batteries, it is necessary to develop new materials that can satisfy all performance requirements, such as mechanical properties, adhesion, and ion conductivity of the electrode binder. Prior art literature

[0005] Republic of Korea Published Patent Application No. 10-2018-0007335 (January 22, 2018) The problem to be solved

[0006] One aspect of the present invention provides a composition for a secondary battery binder that can simultaneously secure excellent stability, lifespan, and ion conductivity characteristics of the battery.

[0007] Another aspect of the present invention provides a secondary battery binder manufactured from the composition for the secondary battery binder.

[0008] Another aspect of the present invention provides an electrode and a secondary battery using the secondary battery binder. means of solving the problem

[0009] One embodiment of the present invention provides a composition for a secondary battery binder comprising: (A) a crosslinkable monomer comprising an alkylene oxide unit; and (B) one or more polymers selected from (b1) a mixture of polyvinyl alcohol and polyacrylic acid, (b2) a polyvinyl alcohol-graft-polyacrylic acid copolymer, (b3) a polyvinyl alcohol-graft-polyacrylic acid-co-polyalkylene glycol (meth)acrylate copolymer and salts thereof.

[0010] The crosslinkable monomer containing the above alkylene oxide unit may be a polyfunctional epoxy compound.

[0011] The weight-average molecular weight of the above polyvinyl alcohol may be 50,000 to 500,000 g / mol.

[0012] The viscosity-average molecular weight of the above polyacrylic acid may be 100,000 to 500,000 g / mol.

[0013] The above polymer may contain 1 to 10 parts by weight of a crosslinkable monomer per 100 parts by weight of the polymer.

[0014] The above mixture may contain polyvinyl alcohol and polyacrylic acid in a weight ratio of 3:7 to 7:3.

[0015] The above polyvinyl alcohol-graft-polyacrylic acid copolymer may have 30 to 70 weight percent of polyacrylic acid grafted to the copolymer.

[0016] The above (b3) polyvinyl alcohol-graft-polyacrylic acid-co-polyalkylene glycol (meth)acrylate copolymer may be one in which 30 to 70 weight% of polyacrylic acid-co-polyalkylene glycol (meth)acrylate is grafted onto the copolymer.

[0017] Another aspect of the present invention provides a secondary battery binder prepared from the composition for the secondary battery binder.

[0018] According to one embodiment, the binder may be a secondary battery binder, such as a water-based binder for secondary battery electrodes.

[0019] Another aspect of the present invention provides an electrode slurry composition comprising an electrode active material; a conductive material; the binder; and a solvent.

[0020] According to one embodiment, the electrode slurry composition may contain 1 to 30 weight percent of a binder relative to the total weight of the solid content.

[0021] The above solvent may be an aqueous solvent.

[0022] Another aspect of the present invention provides an electrode comprising: a current collector; and an electrode active material layer formed on the current collector and prepared from an electrode slurry composition according to one aspect; and a secondary battery comprising the same. Effects of the invention

[0023] A binder prepared from a binder composition according to one embodiment of the present invention can satisfy excellent mechanical properties, adhesion, and ion conductivity characteristics when applied to an electrode of a secondary battery. Specifically, the binder according to one embodiment can effectively maintain a balance of mechanical properties of ductility and rigidity, thereby suppressing the volume expansion phenomenon of the electrode and maintaining the electrode material in a stable state, and also has excellent adhesion, which can ensure improved lifespan and reliability of the battery. At the same time, the binder according to one embodiment has excellent ion conductivity and electrolyte permeability, which can also improve battery performance.

[0024] In other words, a binder according to one embodiment can provide a secondary battery that satisfies excellent performance, stability, and lifespan characteristics. Specific details for implementing the invention

[0025] Unless otherwise defined in this specification, all technical and scientific terms have the same meaning as generally understood by those skilled in the art to which the present invention pertains. The terms used in the description herein are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention.

[0026] The singular form used in this specification is intended to include the plural form unless specifically indicated otherwise in the context.

[0027] Throughout this specification, the terms “comprising,” “having,” “containing,” or “having” any component mean that, unless specifically stated otherwise, other components are not excluded but may be included, and do not exclude elements, materials, or processes not additionally listed.

[0028] The numerical ranges used herein include lower and upper limits and all values ​​within the range, increments logically derived from the form and width of the defined range, all of which are limited, and all possible combinations of upper and lower limits of the numerical range defined in different forms. Unless otherwise specifically defined in this specification, values ​​outside the numerical range that may occur due to experimental error or rounding are also included in the defined numerical range.

[0029] Unless otherwise specifically defined in this specification, “about” may be considered to be a value within 30%, 25%, 20%, 15%, 10%, or 5% of the specified value.

[0030] In this specification, "(meth)acrylate" means including acrylate or methacrylate.

[0031] The present disclosure will be described in detail below. However, this is merely illustrative and the present disclosure is not limited to the specific embodiments described illustratively.

[0032] One embodiment of the present invention provides a composition for a secondary battery binder comprising: (A) a crosslinkable monomer comprising an alkylene oxide unit; and (B) one or more polymers selected from (b1) a mixture of polyvinyl alcohol and polyacrylic acid, (b2) a polyvinyl alcohol-graft-polyacrylic acid copolymer, (b3) a polyvinyl alcohol-graft-polyacrylic acid-co-polyalkylene glycol (meth)acrylate copolymer and salts thereof.

[0033] A binder composition according to one embodiment satisfies the above-described compositional combination, thereby simultaneously securing excellent mechanical properties, adhesion, and ion conductivity characteristics for future use as a binder for secondary batteries.

[0034] A composition for a secondary battery binder according to one embodiment may further include a solvent, and said solvent may be an aqueous solvent, specifically water.

[0035] The crosslinkable monomer containing the above alkylene oxide unit may be used without limitation as long as it is a compound having two or more polymerizable functional groups capable of reacting with the hydroxyl group of the polyvinyl alcohol and the carboxylic acid group of the polyacrylic acid while containing the alkylene oxide unit, and as an example, it may be a polyfunctional epoxy compound.

[0036] The above alkylene oxide unit may be, for example, a (C1-C7)alkylene oxide unit, or a (C1-C5)alkylene oxide unit, or a (C1-C3)alkylene oxide unit, and specifically may be an ethylene oxide unit or a propylene oxide unit.

[0037] The polyfunctional epoxy compound containing the above alkylene oxide unit may be selected from, for example, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, but is not limited thereto.

[0038] When the above-mentioned crosslinkable monomer includes alkylene oxide units as repeating units, the number average molecular weight of the above-mentioned crosslinkable monomer is not specifically limited within the range for achieving the purpose of the present invention, but, for example, it may be 100 to 5,000 g / mol, or 200 to 3,000 g / mol, or 400 to 2,000 g / mol, but is not limited thereto.

[0039] The weight-average molecular weight of the above poly(vinyl alcohol), PVA, may be 10,000 to 500,000 g / mol, specifically 50,000 to 500,000 g / mol, or 100,000 to 400,000 g / mol, but is not limited thereto. The viscosity-average molecular weight of the above poly(acrylic acid), PAA, may be 10,000 to 500,000 g / mol, specifically 50,000 to 500,000 g / mol, or 100,000 to 500,000 g / mol, but is not limited thereto.

[0040] When satisfying the above molecular weight range, it has excellent solubility in aqueous solvents, and subsequently, it can further enhance the simultaneous improvement effect of the binder's own mechanical properties, adhesion, and ion conductivity.

[0041] In addition, a composition for a secondary battery binder according to one embodiment may include 1 to 30 parts by weight, or 20 parts by weight, or 1 to 10 parts by weight of a crosslinkable monomer (A) with respect to 100 parts by weight of the polymer (B), and further improve the simultaneous improvement effect of the ion conductivity, adhesion, and mechanical properties of the binder.

[0042] A composition for a secondary battery binder according to one embodiment is not particularly limited as long as it achieves the purpose of the present invention, but, for example, may include the polymer (B) in an amount of 1 to 30 weight%, or 3 to 30 weight%, or 3 to 20 weight%, or 3 to 15 weight% with respect to the total weight of the composition.

[0043] The above (b1) mixture containing polyvinyl alcohol and polyacrylic acid may contain polyvinyl alcohol and polyacrylic acid in a weight ratio of 3:7 to 7:3, or 4:6 to 6:4, or 5:5, but is not specifically limited.

[0044] The above (b2) polyvinyl alcohol-graft-polyacrylic acid copolymer may be grafted with 30 to 70 weight% or 40 to 60 weight% of polyacrylic acid with respect to the copolymer, specifically 50 weight% grafted, but is not specifically limited. However, since the polymer satisfies the above-described range, it may be preferred as it can further enhance the effect of simultaneously improving the adhesive strength and mechanical properties of the binder.

[0045] In addition, the above (b3) polyvinyl alcohol-graft-polyacrylic acid-co-polyalkylene glycol (meth)acrylate copolymer may be one in which 30 to 70 weight%, or 40 to 60 weight%, or 50 weight% of polyacrylic acid-co-polyalkylene glycol (meth)acrylate is grafted onto the copolymer. Specifically, the above (b3) may be one in which acrylic acid and polyalkylene glycol (meth)acrylate are graft copolymerized together on a polyvinyl alcohol main chain.

[0046] In the above (b3), the polyalkylene glycol (meth)acrylate may be selected from, for example, polyethylene glycol methyl ether acrylate, polyethylene glycol acrylate, and polyethylene glycol methacrylate, but is not limited thereto.

[0047] Specific examples of the above (b3) polyvinyl alcohol-graft-polyacrylic acid copolymer may include polyvinyl alcohol-graft-polyacrylic acid copolymer (PVA-g-PAA), polyvinyl alcohol-graft-polyacrylic acid-co-polyethylene glycol methyl ether acrylate copolymer (PVA-g-PAA-co-PPEGMA), and polyvinyl alcohol-graft-polyacrylic acid-co-polyethylene glycol acrylate copolymer (PVA-g-PAA-co-PPEGA).

[0048] According to one embodiment, the composition for a secondary battery binder may be an aqueous binder composition for a secondary battery electrode, and specifically, may be an aqueous binder composition for a negative electrode.

[0049] Another aspect of the present invention provides a secondary battery binder manufactured from the above-described composition for a secondary battery binder.

[0050] Specifically, according to one embodiment, a secondary battery binder may refer to a form in which a crosslinkable monomer-derived unit comprising an alkylene oxide unit; and a copolymer comprising a polyvinyl alcohol-derived unit and a polyacrylic acid-derived unit are crosslinked to each other, or a salt thereof.

[0051] The description of the crosslinkable monomer containing the above-mentioned alkylene oxide, polyvinyl alcohol, and polyacrylic acid is omitted as it is as described above.

[0052] According to one embodiment, the binder may be an aqueous binder for a secondary battery electrode, and specifically, may be an aqueous binder for a negative electrode.

[0053] Another aspect of the present invention provides an electrode slurry composition comprising the secondary battery binder and an electrode manufactured therefrom.

[0054] The following describes an electrode slurry composition and an electrode according to one embodiment, but it is obvious that, except for including a binder according to one embodiment, it can be manufactured into a structure known in the art using conventional manufacturing methods and materials in the art.

[0055] An electrode slurry composition according to one embodiment comprises an electrode active material; a conductive material; a binder; and a solvent, wherein the binder is a binder prepared from the composition for a secondary battery binder according to one embodiment.

[0056] The above electrode slurry composition may contain a solid content of 10 to 50 weight%, or 20 to 50 weight%, or 20 to 40 weight% based on the total weight of the composition, and may contain a binder of 1 to 30 weight%, or 5 to 30 weight%, or 10 to 30 weight% based on the total weight of the solid content.

[0057] A slurry composition for an electrode according to one embodiment may be a slurry composition for a cathode, and the solvent may be an aqueous solvent and specifically may be water.

[0058] The above electrode active material may specifically be a negative electrode active material, and materials conventional in this technical field may be used; non-limiting examples include any one carbon-based material selected from soft carbon, hard carbon, artificial graphite, natural graphite, expanded graphite, carbon fiber, non-blackened carbon, carbon black, carbon nanotube, acetylene black, ketjen black, graphene, fullerene, activated carbon, and mesocarbon microbeads; Si, SiO x (O <x<2), Si / C, 및 SiO / C 중에서 선택된 어느 하나의 규소계 물질;에서 선택되는 어느 하나 또는 둘 이상인 것일 수 있다.

[0059] The above conductive material may include carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; conductive fibers such as carbon fibers, metal fibers, etc.; metal powders such as carbon fluoride, aluminum, nickel powder, etc.; conductive whiskey such as zinc oxide, potassium titanate, etc.; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc., but is not particularly limited as long as it possesses conductivity without causing chemical changes in the battery.

[0060] Another aspect of the present invention provides a secondary battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, which can be manufactured into a structure known in the art using conventional manufacturing methods and materials in the art, except that the positive electrode and / or negative electrode comprises an electrode binder according to one aspect.

[0061] As an example, when a cell (half-cell) according to the present invention is charged and discharged at room temperature (25°C) under the following conditions, the initial efficiency is 80% or more, preferably 85% or more, and the initial discharge capacity is 1200 or more, 1300 or more, 1400 or more, 1500 or more, 2000 mAh / g or more, up to 3000 mAh / g, and the discharge capacity retention rate after 50 cycles is 85% or more, 90% or more, 95% or more, 99%.

[0062] The above-described embodiment will be explained in more detail below through examples. However, the following examples are for illustrative purposes only and do not limit the scope of the claims.

[0063] [Preparation Example 1] Poly(acylic acid) (PAA) aqueous solution

[0064] Add 190g of distilled water to a 500mL bottle and PAA resin (Aldrich, M v 10g of (~450,000) was added in small amounts and dissolved in a shaker at room temperature for 24 hours to prepare 200g of a 5wt% PAA aqueous solution.

[0065] [Preparation Example 2] Poly(vinyl alcohol) (PVA) aqueous solution

[0066] In a 1-liter flask, PVA resin (Aldrich, M w Add 30g of 146,000~186,000 (sabsorption 99+%) and 270g of distilled water, and while stirring with a mechanical stirrer, raise the temperature to 95 After raising the temperature to ℃ and stirring for 6 hours to completely dissolve it, the solution was cooled to room temperature to prepare 300g of a 10wt% PVA aqueous solution.

[0067] [Preparation Example 3] Polyvinyl alcohol-grafted-polyacrylic acid (PVA-g-PAA) aqueous solution

[0068] After thoroughly purging a 1-liter 4-neck flask reaction vessel equipped with a condenser and a nitrogen inlet with nitrogen for more than 30 minutes, 20g of PVA resin (Aldrich, Mw 146,000~186,000, degree of saponification 99+%) was added, followed by 180g of distilled water. After stirring with a mechanical stirrer for more than 30 minutes, the temperature was raised to 95℃ and stirred for 6 hours to prepare an aqueous PVA solution. Then, the PVA solution was lowered to 65℃, 0.00512mol of potassium persulfate (K2S2O8, Aldrich, ACS reagent 99.0% or higher) and 0.00307mol of sodium bisulfite (NaHSO3, Aldrich, ACS reagent) were added, and the mixture was stirred for 20 minutes. Subsequently, 20g of acrylic acid (Aldrich, anhydrous, 99%, MEHQ 200ppm) was added and the reaction was carried out while stirring for 6 hours to obtain an aqueous solution of approximately 18.2wt% of PVA-g-PAA copolymer.

[0069] [Preparation Example 4] Polyvinyl alcohol-grafted-polyacrylic acid-co-polyethylene glycol methyl ether acrylate (PVA-g-PAA-co-PPEGMA) aqueous solution

[0070] The above preparation was carried out in the same manner as in Preparation Example 3, except that instead of adding acrylic acid alone, 15g of acrylic acid (Aldrich, anhydrous, 99%, MEHQ 200ppm) and 5g of polyethylene glycol methyl ether acrylate (PEGMA, Aldrich, average Mn 480, MEHQ 100ppm, BHT 100ppm) were added.

[0071] [Example 1]

[0072] Preparation of a binder composition

[0073] 50g of the 5wt% PAA aqueous solution of Preparation Example 1 and 25g of the 10wt% PVA aqueous solution of Preparation Example 2 were mixed using a mechanical stirrer to prepare a solution of approximately 6.67wt% polyvinyl alcohol and polyacrylic acid (PVA / PAA), and 0.25g of polyethylene glycol diglycidyl ether (PEGDE, Mn=500) was added to prepare the binder composition of Example 1.

[0074] The above binder composition was stirred at room temperature for 24 hours to obtain an aqueous solution (binder aqueous solution) containing the binder of Example 1, and was used in the aqueous solution state for manufacturing electrodes.

[0075] Electrode and battery manufacturing

[0076] The above-mentioned aqueous binder solution, conductive material (Super P), and cathode active material (Si 50 nm) were mixed in an aqueous solution to achieve a solid-based weight ratio of 2:2:6 and a solid concentration of 30 wt%, and dispersed using a homomixer to prepare a cathode slurry composition. The prepared cathode slurry composition was applied to a copper foil current collector and subjected to primary drying at 110°C for 0.5 hours. Subsequently, for coin cell fabrication, the cathode was manufactured by punching, pressing, and welding, followed by vacuum drying in a vacuum oven at a drying temperature of 350°C for 2 hours. The loading amount of the manufactured cathode was 0.6 mg / cm². 2 A lithium secondary battery half-cell was manufactured using the cathode prepared in this way, lithium metal as the counter electrode, and a porous polypropylene film as the separator. At this time, a mixed solution of ethylene carbonate and diethylene carbonate (3:7 volume ratio) in which 1M LiPF6 was dissolved was used as the electrolyte. Cell assembly was carried out in a glove box filled with argon gas, and after cell assembly, battery characteristics were evaluated using a 100mA charge / discharger.

[0077] [Example 2]

[0078] 50g of the 5wt% PAA aqueous solution of Preparation Example 1 above, 27.5g of the 10wt% PVA aqueous solution of Preparation Example 2 above, and 5g of the 18.2wt% PVA-g-PAA aqueous solution of Preparation Example 3 above were added and stirred with a mechanical stirrer to prepare a mixed aqueous solution of about 7.16wt%, and 0.375g of PEGDE (Mn=500) was added thereto to prepare the binder composition of Example 2, and the process was carried out in the same manner as Example 1.

[0079] [Example 3]

[0080] The above Example 2 was carried out in the same manner, except that PVA-g-PAA-co-PPEGMA obtained in Preparation Example 4 was used instead of PVA-g-PAA.

[0081] [Example 4]

[0082] The procedure was carried out in the same manner except that 0.6g of NaOH was added to 75g of the aqueous binder solution of Example 1 and stirred at room temperature for 24 hours to obtain an aqueous binder solution with Na cations substituted therein.

[0083] [Comparative Example 1]

[0084] 27.5g of the PVA aqueous solution from Preparation Example 2 was diluted to a concentration of approximately 10 wt% by adding 22.5g of distilled water, then adjusted to a pH of 3 using a 1N hydrochloric acid aqueous solution, and finally, 0.375g of PEGDE (Mn=500) was added to prepare the binder composition of Comparative Example 1. Subsequently, the process was carried out in the same manner as in Example 1.

[0085] [Comparative Example 2]

[0086] 22.5g of distilled water was additionally added to 27.5g of the PVA-g-PAA aqueous solution of Preparation Example 3 to dilute it to a concentration of about 10wt%, and then 0.5g of a 10wt% glyoxal aqueous solution was added to prepare the binder composition of Comparative Example 2. Subsequently, the procedure was carried out in the same manner as in Example 1.

[0087] [Comparative Example 3]

[0088] The above Example 1 was carried out in the same manner, except that PEGDE was not used when preparing the binder composition.

[0089] <Evaluation Example>

[0090] Evaluation 1. Battery Characteristics Evaluation

[0091] The cell (half-cell) obtained in the above examples and comparative examples for evaluating battery characteristics was charged and discharged at 0.05C at room temperature (25℃) to observe the initial formation efficiency, and charged and discharged at 0.5C for evaluating the discharge retention rate. Charging was performed by fully charging with a constant current to an upper limit voltage of 0.01V, and discharging was performed by discharging with a constant current until the voltage reached 1.4V. The charge / discharge cycle characteristics were evaluated by performing 50 charge / discharge cycles. For a more accurate evaluation, four cells under the same conditions were prepared and evaluated simultaneously, and the average value results are shown in Table 1 below.

[0092] Initialization efficiency (%) Initial discharge capacity (mAh / g) Discharge capacity @50cycle(mAh / g) Discharge capacity retention rate @ 50 cycles (%) Example 1 82 1350 1200 89 Example 2 86 1450 1400 96 Example 3 84 2300 2000 87 Example 4 86 1500 1400 93 Comparative Example 1 76 1300 750 58 Comparative Example 2 67 1100 100 9 Comparative Example 3 77 1200 400 33

[0093] Referring to Table 1 above, it can be seen that the electrode according to the embodiment of the present invention exhibits excellent initial performance efficiency, initial discharge capacity, and discharge capacity retention rate. This is expected to be the result of the binder according to the present invention containing PAA derivative units, PVA derivative units, and alkylene oxide crosslinking units, which allows for the maintenance of mechanical properties of flexibility and rigidity, thereby effectively improving the volume expansion phenomenon of the active material and enhancing adhesion.

[0094] On the other hand, Comparative Examples 1 to 3 are cases in which none of the essential constituent units of the binder of the present invention are included, and it can be seen that the capacity retention rate decreases rapidly.

[0095] As described above, the present invention has been explained by specific details and limited embodiments; however, this is provided merely to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. Those skilled in the art can make various modifications and variations from this description.

Claims

Claim 1 A composition for a secondary battery binder comprising: (A) a polyfunctional epoxy compound containing alkylene oxide units; and (B) one or more polymers selected from (b1) a mixture of polyvinyl alcohol and polyacrylic acid, (b2) a polyvinyl alcohol-graft-polyacrylic acid copolymer, (b3) a polyvinyl alcohol-graft-polyacrylic acid-co-polyalkylene glycol (meth)acrylate copolymer and salts thereof. Claim 2 delete Claim 3 A composition for a secondary battery binder according to claim 1, wherein the weight-average molecular weight of the polyvinyl alcohol is 50,000 to 500,000 g / mol. Claim 4 A composition for a secondary battery binder according to claim 1, wherein the viscosity average molecular weight of the polyacrylic acid is 100,000 to 500,000 g / mol. Claim 5 A composition for a secondary battery binder according to claim 1, comprising 1 to 10 parts by weight of (A) a polyfunctional epoxy compound per 100 parts by weight of (B) polymer. Claim 6 A composition for a secondary battery binder according to claim 1, wherein the mixture (b1) comprises polyvinyl alcohol and polyacrylic acid in a weight ratio of 3:7 to 7:

3. Claim 7 A composition for a secondary battery binder according to claim 1, wherein the (b2) polyvinyl alcohol-graft-polyacrylic acid copolymer is grafted with 30 to 70 weight% of polyacrylic acid with respect to the copolymer. Claim 8 A composition for a secondary battery binder according to claim 1, wherein (b3) the polyvinyl alcohol-graft-polyacrylic acid-co-polyalkylene glycol (meth)acrylate copolymer is a copolymer in which 30 to 70 weight% of polyacrylic acid-co-polyalkylene glycol (meth)acrylate is grafted. Claim 9 In claim 1, the composition for a secondary battery binder is a water-based binder composition for a secondary battery electrode. Claim 10 A secondary battery binder manufactured from a composition for a secondary battery binder according to any one of claims 1 and 3 to 9. Claim 11 An electrode slurry composition comprising an electrode active material; a conductive material; a binder according to claim 10; and a solvent. Claim 12 The electrode slurry composition according to claim 11, wherein the electrode slurry composition comprises 1 to 30 weight percent of a binder based on the total weight of the solid content. Claim 13 In claim 11, the above solvent is an aqueous solvent, an electrode slurry composition. Claim 14 An electrode comprising: a current collector; and an electrode active material layer formed on the current collector and prepared from an electrode slurry composition according to claim 11. Claim 15 A secondary battery comprising an electrode according to paragraph 14.

Citation Information

Patent Citations

  • Composition, composition for positive electrode, slurry for positive electrode, positive electrode and secondary battery

    KR1020230050407A